A Systematic Review and Meta-Analysis of Randomized Controlled Trials for Electroacupuncture Treatment of Migraine - Song S; Chen H (Journal of Pain Research)
ShiWei Song,1 Hao Chen2 1Department of Traditional Chinese Medicine, Sichuan Taikang Hospital, Chengdu, Sichuan, People’s Republic of China; 2Chengdu University of Traditional Chinese Medicine CN, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: ShiWei Song, Sichuan Taikang Hospital, No. 881 Xianghe 1st Street, Huayang Community, Tianfu New Area, Chengdu, Sichuan, People’s Republic of China, Email songsw7294@126.comPurpose: Numerous clinical studies have shown that patients with migraine can benefit from electroacupuncture treatment. However, there are no published systematic reviews and meta-analyses of pure electroacupuncture for migraine. Therefore, we conducted a meta-analysis to evaluate the efficacy of pure electroacupuncture as a standalone treatment for migraine patients.Patients and Methods: We searched Six electronic databases. All from the inception to August 1st, 2024. In the literature, clinical investigators evaluated the efficacy and safety of electroacupuncture as the primary treatment for migraine. Researchers assessed the quality of the studies using the Cochrane Handbook for Systematic Reviews of Interventions. The Review Manager 5.4 software was used to perform statistical analysis.Results: Ten randomized controlled trials involving 1161 people were included. The meta-analysis yielded a substantial result: the application of pure electroacupuncture significantly improved the effective rate compared to the control group. In the visual analogue scale score, the present study found no significant difference between electroacupuncture and Western medicine as standalone treatments. Regarding migraine-associated symptom scores, the experimental group exhibited no superiority in comparison to the control group. Moreover, following the intervention, several significant changes were observed in the secondary outcome indicators between the two groups, including cerebral arterial blood flow velocity, the migraine attack days, the lasting time of headache remission, mean time of the headache attack, duration of the headache attack, and the migraine-specific quality of life questionnaire score, with the results proving to be statistically significant.Conclusion: The results of the analysis suggested that pure electroacupuncture is beneficial for migraine patients, but it remains difficult to obtain comprehensive data. Our study is supported by evidence of low to moderate quality. It is necessary to further confirm the efficacy of pure electroacupuncture for migraine with higher-quality clinical research.Keywords: electroacupuncture, migraine, meta-analysis, randomized controlled trials, systematic review